2018
DOI: 10.3892/mmr.2018.8511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of T helper cell 1/T helper cell 2 balance and nuclear factor-κB on white matter injury in premature neonates

Abstract: Incidence of white matter injury (WMI), which is featured as softening of white matter tissues, has recently increased. Previous studies have demonstrated a close correlation between T helper cell 1 and T helper cell 2 (Th1/Th2) imbalance and nuclear factor‑κB (NF‑κB) with brain disease. Their role in premature WMI, however, remains to be illustrated. Serum samples were collected from 60 premature WMI neonates, plus another control group of 60 premature babies without WMI. Patients were further divided into mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, we did not observe increases in the levels of Th1 or Th17 cytokines in the serum of NE patients, suggesting that T cell activation may be restricted to the brain. Future studies are required to determine if the numerical changes reflect movement of B cells and T cells to the brain or whether particular subsets of these cells, such as regulatory B cells (Bodhankar et al, 2013) or Th1, Th2, Th17 or regulatory T cells (Su et al, 2018), are numerically altered. Future studies are also required to determine if the increased numbers of B cells in patients with NE are associated with higher serum immunoglobulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe increases in the levels of Th1 or Th17 cytokines in the serum of NE patients, suggesting that T cell activation may be restricted to the brain. Future studies are required to determine if the numerical changes reflect movement of B cells and T cells to the brain or whether particular subsets of these cells, such as regulatory B cells (Bodhankar et al, 2013) or Th1, Th2, Th17 or regulatory T cells (Su et al, 2018), are numerically altered. Future studies are also required to determine if the increased numbers of B cells in patients with NE are associated with higher serum immunoglobulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta seems to be more vulnerable after ART treatment. Studies have shown that there is a significant increase in the expression of NFκB in ART placental tissue (19), and the upregulation of NFκB has been confirmed to be related to the pathogenesis of WMI (20,21). In addition, in the critical early period of brain development, fetal steroid hormones are believed to play a role in the epigenetic fetal programming mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 60 white matter injury (WMI) premature neonates showed a correlation between low levels of IL-4 and IL-10 and high levels of IL-2, TNF-α and NF-κB activation with the severity of the injury. This imbalance in Th1/Th2 cytokine production along with the upregulation of NF-κB have been suggested as potential biomarkers for the early diagnosis and treatment of WMI in premature neonates ( Su et al., 2018 ). IL-6, IL-4, IL-12, and IL-17 are elevated in neonates with NE and neonatal arterial ischemic stroke (NAIS).…”
Section: Conventional T Cells In Nementioning
confidence: 99%